ANALYSIS OF THE QUALITATIVE STATE OF THE LAND FUND OF THE REPUBLIC OF UZBEKISTAN - Romanyuk Julia; Khamidov McNon (Galaxy International Interdisciplinary Research Journal, 2022)
Centuries-old practice shows that the main sources of viability and prosperity of any state are its land resources and the population living on them. Land resources - the earth’s surface, suitable for human habitation and for any kind of economic activity. Land resources are characterized by the size of the territory and its quality: relief, soil cover and a complex of other natural conditions.